Cultural antinomies of the contemporary serbian society: premodern mentality vs. postmodern identity - Božilović, Nikola T. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2020)
Globalization has permeated all aspects of social life (economic, political, cultural) and affected the daily life of people. Postindustrial society and postmodern culture have made a significant impact on the transformation of identities, which have truly become liquid – multidimensional, discontinuous, decentralized, fragmented, unstable and inconstant. Parallel with this, new tendencies in culture have almost completely narrowed the boundary between high and popular creativity, thus challenging the status of the established, until then recognized values. These changes have also become evident in the contemporary Serbian society, which is obsessed by preserving the tradition and long-developed identities. By chance, that society has had one foot in the postmodern information world, with the other stuck in the quagmire of old habits and misconceptions inherited from the period of premodern social awareness. By analysing crucial value aspects (traditionalism, conformism, authoritarianism and nationalism), the author of this paper attempts to provide an explanation (which is the basic precondition for the resolution) of the ambivalent and, seemingly, inescapable situation in which the culture of Serbian society finds itself.
Keywords: culture; identity; postmodernism; premodern state of society